Detection of bridging veins rupture and subdural haematoma onset using a finite element head model. (March 2019) - Migueis, G.F.J.; Fernandes, F.A.O.; Ptak, M.; Ratajczak, M.; Alves de Sousa, R.J.
Abstract: Background: One of the most severe traumatic brain injuries, the subdural haematoma, is related to damage and rupture of the bridging veins, generating an abnormal collection of blood between the dura mater and arachnoid mater. Current numerical models of these vessels rely on very simple geometries and material laws, limiting its accuracy and bio-fidelity. Methods: In this work, departing from an existing human head numerical model, a realistic geometry for the bridging veins was developed, devoting special attention to the finite elements type employed. A novel and adequate constitutive model including damage behavior was also successfully implemented. Findings: Results attest that vessel tearing onset was correctly captured, after comparison against experiments on cadavers. Interpretation: Doing so, the model allow to precisely predict the individual influence of kinematic parameters such as the pulse duration, linear and rotational accelerations in promoting vessel tearing. Highlights: Detailed numerical modeling of the superior sagittal sinus and 9 pairs of bridging veins Constitutive modeling including elasto-plasticity and ductile damage Integration into a finite element head model and validation against experiments on cadavers